Effect of breastfeeding education and support intervention (BFESI) versus routine care on timely initiation and exclusive breastfeeding in Southwest Ethiopia: study protocol for a cluster randomized controlled trial - Misra Abdulahi; Atle Fretheim; Jeanette H. Magnus (BMC, 2018)
Abstract Background Infant mortality rates are still high in Ethiopia. Breastfeeding is regarded as the simplest and least expensive strategy for reduction of infant mortality rates. Community-based educational and support interventions provided prenatally and postnatally are effective in increasing breastfeeding rates. However, such interventions are not widely implemented in Ethiopia. This study aims to assess the effect of breastfeeding education and support on timely initiation and duration of exclusive breastfeeding. Methods A cluster-randomized controlled trial at the community level will be conducted to compare the effect of breastfeeding education and support versus routine care. The intervention will be provided by Women Development Army leaders who are already in the country's health system using a 40-h WHO breastfeeding counseling course, "Infant and Young Child Feeding Counseling: an integrated course" and the "Training of Trainers Manual for Counseling on Maternal, Infant and Young Child Nutrition" in the local language. Culturally appropriate operational packages of information will be developed for them. Using preset criteria at least 432 pregnant women in their third trimester will be recruited from 36 zones. Visits in the intervention arm include two prenatal visits and 8 postnatal visits. Supervisory visits will be conducted monthly to each intervention zone. Data will be entered into Epi-data version 3.1 and analyzed using STATA version 13.0. All analysis will be done by intention to treat analysis. We will fit mixed-effects linear regression models for the continuous outcomes and mixed-effects linear probability models for the binary outcomes with study zone as random intercept to estimate study arm difference (intervention vs. routine education) adjusted for baseline value of the outcome and additional relevant covariates. The protocol was developed in collaboration with the Jimma Zone and Mana district Health office. Ethical clearance was obtained from the Institutional Review Board of University of Oslo and Jimma University. This study is partly funded by NORAD's NORHED programme. Discussion We expect that the trial will generate findings that can inform breastfeeding policies and practices in Ethiopia. Trial registration ClinicalTrials.gov NCT 03030651 January 25, 2017 version 3 dated 16 July 2018.